Development of Digital Website Qurma (Qudwah Rasulullah Muhammad) About the Story of My Prophet in PAI Learning for Grade 3 Elementary School - Athia, Najwa; Shabrina, Firyal 'Athifah; Devi, Sibtiani; Aeni, Ani Nur (YASIN, 2025)
The use of technology in Islamic Education subjects can provide many significant benefits. Starting from the use of media such as video, audio, and images can help students visualize complex, abstract, and fun religious concepts, making it easier for students to understand learning. This research aims to develop a digital website-based learning media, QURMA (Qudwah Rasulullah Muhammad SAW), which is specifically designed for grade 3 elementary school students. The researchers used the Design and Development (D&D) model method. The research results were obtained after going through a series of processes that the researchers had carried out. The learning media has been in accordance with the assessment obtained from material experts and media experts that the QURMA digital website can be used in the learning process because it has received very good scores in terms of content/material created by the researchers. From the perspective of QURMA digital website users, students and teachers of grade 3 Elementary Schools assessed that the media was very good and should continue to be developed. Thus, the assessment obtained from material experts, media experts, teachers, and grade 3 elementary school students shows that the development of the QURMA digital website is worthy of use.